Stigmata in cutaneous leishmaniasis: Historical and new evidence-based concepts - Mohamed Ahmed Al-Kamel (Our Dermatology Online, 2017)
This report is a part of many articles and studies published by the Regional Leishmaniasis Control Center (RLCC). Willing that this review might enrich understanding of the global epidemiological profile of CL, the author relied on research evidence, his experience and a social survey to highlight historical and current concepts of cutaneous leishmaniasis (CL) as a globally most prevalent and highly stigmatizing form of leishmaniasis disease, introduce new ideologies upon CL-related stigmata, review the most common determinants and implications of CL stigmata; and report a short survey illustrating stigmata experience among some affected patients from Yemen. He also reviewed a successful community-led action to reduce the burden of CL and its related stigmata in Yemen.